Autologous patient-derived exhausted nano T-cells exploit tumor immune evasion to engage an effective cancer therapy - José L. Blaya-Cánovas; Carmen Griñán-Lisón; Isabel Blancas; Juan A. Marchal; César Ramírez-Tortosa; Araceli López-Tejada; Karim Benabdellah; Marina Cortijo-Gutiérrez; M. Victoria Cano-Cortés; Pablo Graván; Saúl A. Navarro-Marchal; Jaime Gómez-Morales; et al. (Molecular Cancer, 2024)
Abstract Background Active targeting by surface-modified nanoplatforms enables a more precise and elevated accumulation of nanoparticles within the tumor, thereby enhancing drug delivery and efficacy for a successful cancer treatment. However, surface functionalization involves complex procedures that increase costs and timelines, presenting challenges for clinical implementation. Biomimetic nanoparticles (BNPs) have emerged as unique drug delivery platforms that overcome the limitations of actively targeted nanoparticles. Nevertheless, BNPs coated with unmodified cells show reduced functionalities such as specific tumor targeting, decreasing the therapeutic efficacy. Those challenges can be overcome by engineering non-patient-derived cells for BNP coating, but these are complex and cost-effective approaches that hinder their wider clinical application. Here we present an immune-driven strategy to improve nanotherapeutic delivery to tumors. Our unique perspective harnesses T-cell exhaustion and tumor immune evasion to develop a groundbreaking new class of BNPs crafted from exhausted T-cells (NExT) of triple-negative breast cancer (TNBC) patients by specific culture methods without sophisticated engineering. Methods NExT were generated by coating PLGA (poly(lactic-co-glycolic acid)) nanoparticles with TNBC-derived T-cells exhausted in vitro by acute activation. Physicochemical characterization of NExT was made by dynamic light scattering, electrophoretic light scattering and transmission electron microscopy, and preservation and orientation of immune checkpoint receptors by flow cytometry. The efficacy of chemotherapy-loaded NExT was assessed in TNBC cell lines in vitro. In vivo toxicity was made in CD1 mice. Biodistribution and therapeutic activity of NExT were determined in cell-line- and autologous patient-derived xenografts in immunodeficient mice. Results We report a cost-effective approach with a good performance that provides NExT naturally endowed with immune checkpoint receptors (PD1, LAG3, TIM3), augmenting specific tumor targeting by engaging cognate ligands, enhancing the therapeutic efficacy of chemotherapy, and disrupting the PD1/PDL1 axis in an immunotherapy-like way. Autologous patient-derived NExT revealed exceptional intratumor accumulation, heightened chemotherapeutic index and efficiency, and targeted the tumor stroma in a PDL1+ patient-derived xenograft model of triple-negative breast cancer. Conclusions These advantages underline the potential of autologous patient-derived NExT to revolutionize tailored adoptive cancer nanotherapy and chemoimmunotherapy, which endorses their widespread clinical application of autologous patient-derived NExT.